Crohn’s disease, diagnosis, and management - Rika Bur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
Crohn’s disease is a rare chronic inflammatory bowel diseases. The cause could be genetic factors, infection, immunology and psychological factors. The exact diagnosis is determined by colonoscopy and histopathology examination.  Keywords: Inflammatory bowel disease, Crohn’s disease